Pengunaan Biochar Berbahan Baku Tempurung Kelapa dan Pelepah Sawit pada Pembibitan Utama Kelapa Sawit (Elaeis guineensis Jacq.) di Medium Gambut - Guzali, Guzali; Adiwirman, Adiwirman; wawan, wawan (Jurnal Agro Teknologi Tropika, 2016)
The study aims to determine the effect of biochar and biochar coconut palm fronds and the appropriate dose for the growth of oil palm seedlings in peat medium. Research using a completely randomized design with 7 treatments and 3 replications. The treatment consists of: A = without biochar, B = biochar coconut shell (BCS) 10 ton ha-1, C = BCS 15 ton ha-1, D = BCS 20 ton ha-1, E = biochar fronds of palm oil (BFPO) 10 ton ha-1, F = BFPO 15 ton ha-1 and G = BFPO 20 ton ha-1.Data were analyzed statistically by analysis of variance and tested by HSD 5%. The results showed granting biochar coconut shells and fronds of palm on peat soils real effect on convolution weevil, while plant height, leaf number, stem length, fresh weight of roots, fresh weight of shoot, fresh weight of the plants, root dry weight, dry weight of the canopy and dry weight of the plant is not pregnant. Giving biochar coconut shell 37.5 g / polybag (15 ton ha-1) may increase 12.46% over the hump convolution without biochar.